Metaheuristics for time-dependent vehicle routing problem with time windows - LIANG, Yun-C (Institutional Knowledge at Singapore Management University, 2022)
Vehicle routing problem (VRP), a combinatorial problem, deals with the vehicle’s capacity visiting a particular set of nodes while its variants attempt to fit real-world scenarios. Our study aims to minimise total travelling time, total distance, and the number of vehicles under time-dependent and time windows constraints (TDVRPTW). The harmony search algorithm (HSA) focuses on the harmony memory and pitch adjustment mechanism for new solution construction. Several local search operators and a roulette wheel for the performance improvement were verified via 56 Solomon’s VRP instances by adding a speed matrix. The performance comparison with a genetic algorithm (GA) was completed with the same number of parameters and ran in the same computer specification to justify its performance. The results show that HSA can outperform the GA in some instances. The research outcomes suggest that HSA can solve TDVRPTW with comparable results to other commonly used metaheuristic approaches.